Ответы и объяснения

2012-11-22T23:11:20+04:00

если правильно я поняла то это след уравнения:

0,5*(2х-5)-8= -6,5         (9-4х)/8+0,875= 1        6,8*(5х-24)+2,3=4    (4х-9)*2,6+3,8=22 

х-2,5-8=-6,5                 9-4х=(1-0,875)*8          5х-24=(4-2,3)/6,8     4х-9=(22-3,8)/2,6

х=2,5+8-6,5= 4             9-4х=1                         5х=24,25                  4х= 7+9=16

х=4                              8=4х                            х=24,25/5=4,85        х=16/4=4

                                   х=2                              х=4,85                      х=4